A novel alkaline protease from alkaliphilic Idiomarina sp. C9-1 with potential application for eco-friendly enzymatic dehairing in the leather industry. Issue 1 (December 2018) - Zhou, Cheng; Qin, Hongliang; Chen, Xiujuan; Zhang, Yan; Xue, Yanfen; Ma, Yanhe
Abstract Alkaline proteases have a myriad of potential applications in many industrial processes such as detergent, food and feed production, waste management and the leather industry. In this study, we isolated several alkaline protease producing bacteria from soda lake soil samples. A novel serine alkaline protease (AprA) gene from alkaliphilicIdiomarina sp. C9-1 was cloned and expressed inEscherichia coli . The purified AprA and its pre-peptidase C-terminal (PPC) domain-truncated enzyme (AprA-PPC) showed maximum activity at pH 10.5 and 60 °C, and were active and stable in a wide range of pH and temperature. Ca2+ significantly improved the thermostability and increased the optimal temperature to 70 °C. Furthermore, both AprA and AprA-PPC showed good tolerance to surfactants and oxidizing and reducing agents. We found that the PPC domain contributed to AprA activity, thermostability and surfactant tolerance. With casein as substrate, AprA and AprA-PPC showed the highest specific activity of 42567.1 U mg−1 and 99511.9 U mg−1, theK m values of 3.76 mg ml−1 and 3.98 mg ml−1, and theV max values of 57538.5 U mg−1 and 108722.1 U mg−1, respectively. Secreted expression of AprA-PPC inBacillus subtilis after 48 h cultivation resulted in yield of 4935.5 U ml−1 with productivity of 102.8 U ml−1 h−1, which is the highest reported in literature to date. Without adding any lime or sodium sulfide, both of which are harmful pollutants, AprA-PPC was effective in dehairing cattle hide and skins of goat, pig and rabbit in 8–12 h without causing significant damage to hairs and grain surface. Our results suggest that AprA-PPC may have great potentials for ecofriendly dehairing of animal skins in the leather industry.